[FeFe]‐Hydrogenase with Chalcogenide Substitutions at the H‐Cluster Maintains Full H2 Evolution Activity. (23rd May 2016) - Noth, Jens; Esselborn, Julian; Güldenhaupt, Jörn; Brünje, Annika; Sawyer, Anne; Apfel, Ulf‐Peter; Gerwert, Klaus; Hofmann, Eckhard; Winkler, Martin; Happe, Thomas
Abstract: The [FeFe]‐hydrogenase HYDA1 from Chlamydomonas reinhardtii is particularly amenable to biochemical and biophysical characterization because the H‐cluster in the active site is the only inorganic cofactor present. Herein, we present the complete chemical incorporation of the H‐cluster into the HYDA1‐apoprotein scaffold and, furthermore, the successful replacement of sulfur in the native [4FeH ] cluster with selenium. The crystal structure of the reconstituted pre‐mature HYDA1[4Fe4Se]H protein was determined, and a catalytically intact artificial H‐cluster variant was generated upon in vitro maturation. Full hydrogen evolution activity as well as native‐like composition and behavior of the redesigned enzyme were verified through kinetic assays, FTIR spectroscopy, and X‐ray structure analysis. These findings reveal that even a bioinorganic active site with exceptional complexity can exhibit a surprising level of compositional plasticity.